Effect of Final Felling on Natural Regeneration III Rhizophora dominated Forests of Matang Mangrove Reserve - Srivastava, P. B. L.; Shaffie, Abdullah Sani (1979)
A study was undertaken to determine the effect of final felling an the natural regeneration of mangrove forests in matang Reserve. Two adjoining compartments (nos. 38 and 39) having typical Rhizophora forests and belonging to innundation classes III and IV 'were located from which three plots 'which were ready for felling and another three which had been felled during the past six months, were sampled. Although, four species were recorded bath at pre-felling and post-felling stages, the most common were Rhizophora apiculata and Bruguiera parviflora. The farmer 'was more abundant than the latter in most of the plats. All the plots were highly stacked particularly with Rhizophora seedlings. Both the species shOwed considerable variation in different height classes in between the plats bath at prefelling and post felling stages. Before felling the maximum number of seedlings of Rhizophora belonged to l' - 5' height class (720/0) those below l' and between 5 -10' accounted for 25 per cent and 3 per cent respectively. After felling, the pattern was the same but the proportion of the seedlings in l' - 5' group decreased to 54 per cent, Those below l' increased in number. A pronounced deleterious effect was not observed on the stocking of Rhizophora seedlings· in compartment 38 after lagging, The reverse was true in the overcrowded compartment 39, In the case of B, parviflora, the highest number of seedlings belonged to the HI (below 1') class (over 800/0 of the total) both before and after logging. An increase of about 16% was recorded in the number of this species in lagged-aver plat 6. However, mast of the plats in the present study were found to be adequately stocked with Rhizophora seedlings,